The potential of porcelain waste as sand replacement to produce high strength concrete - Jasim, Mohammed Jamal (2021)
Presently, green environment has been the biggest challenge in building and construction industries. An alternative in promotion to green environment is an effective and efficient recycling system by reusing solid waste materials like porcelain waste (PW). Recently, due to high demand in the construction industries, consumption of sand has increased which lead to series of problems such as natural sand depletion and its negative impact on the environment. This research is to investigate the possibility of using porcelain waste as sand replacement in the concrete production. Three different samples of concrete have been casted (cubes, cylinders and beams), with different sizes, the water cement ratio adopted is 0.5 and 0.37 when superplasticizer was added with mix proportion of concrete 1:1.5:3. The sand was replaced with porcelain waste at 10 %, 20 %, 30 %, 40 % and 50 %. Laboratory investigation were focused on examining the mechanical properties and thermal properties of the porcelain waste concrete (PWC). This involved compressive strength, splitting tensile strength, flexural strength and thermal conductivity, specific heat capacity, thermal diffusivity. The physical properties examined are porosity, water absorption and density. The chemical composition of PW material was completed by using X-ray fluorescence (XRF) technique. The distribution of porcelain waste particles inside the concrete were examined using optical microscope. Furthermore, mineralogical configuration of PWC were determined using X-ray diffraction (XRD) technique. At 50 % replacement the compressive strength of concrete at 60 days was 56.5 MPa and 75.2 MPa for 0.5 and 0.37 w/c ratio respectively, which shows an improvement of 17.2 % and 29.2 % over the concrete with natural sand. Similarly, specific heat capacity and porosity for concrete at 60 days was shows an improvement of 29.3 %, 28.6 % and 62.8 %, 36 % for 0.5 and 0.37 w/c ratio respectively. Therefore, 50 % sand replacement with PW resulted in concrete with excellent performance and it has the quality to be used as partial replacement of sand.